Internalization Of Islamic Educational Values In Sharia Business Ethics Among MSMEs - Ichsan, Muhammad (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2026)
This study examines the internalization of Islamic educational values in shaping Sharia business ethics among Micro, Small, and Medium Enterprises (MSMEs) from the perspective of Islamic economics. The main issue addressed in this research is the persistent gap between the normative understanding of Islamic values and their practical implementation in MSME business activities, resulting in Sharia business ethics that are not yet fully institutionalized as a sustainable business culture. The objective of this study is to analyze how the internalization process of Islamic educational values contributes to the formation of sustainable Sharia business ethics within MSMEs. This research adopts a qualitative research design utilizing a library research (literature based) methodology with a descriptive analytical approach. The study systematically collects secondary data from a wide range of scholarly sources, including peer-reviewed journal articles, academic books, and authoritative publications related to Islamic education, Sharia business ethics, and Islamic economics. The data analysis is conducted through a content analysis technique, involving systematic reading, coding, categorization, and interpretation of key concepts and theoretical constructs found within the selected literature. This process enables the synthesis of relevant ideas and the identification of conceptual patterns, relationships, and scholarly perspectives. The findings reveal that the internalization of Islamic educational values-such as tawhid (monotheism), amanah (trustworthiness), adl (justice), and ihsan (excellence) serves as the fundamental foundation in shaping ethical, honest, and responsible business behavior. The internalization process occurs through three stages, namely value transformation, value transaction, and value transinternalization, which determine the extent to which these values become embedded in the character of MSME actors. However, in practice, the dominance of profit-oriented behavior often hinders the full implementation of these values consistently in business activities. The study concludes that value internalization is a key determinant in the development of Sharia business ethics among MSMEs. Therefore, strengthening value based Islamic education is strategically essential in building MSMEs that are ethical, sustainable, and oriented toward barakah (divine blessing) and social welfare